A Study about Language Used toward Gender Differences between Females and Males in Social Context - Lovarinka Jihan Shafira (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study was purposed to investigate gender differences impact to the language used in widely social context. Library research method was conducted in this study. There were no population and sample in this study. As the author only need books and pieces of research to find out the answer. The auhor was using thematical analysis technique to analyze. The results showed that the gender differences affected to the language used, such as dialects, phonological, morphological structure and how they communicate, which are have unique characteristics every origin/language.